A novel POU homeodomain gene specifically expressed in cells of the developing mammalian nervous system. - Collum, R G (1992)
We report the isolation of a novel human POU domain encoding gene named RDC-1. The POU domain of the RDC-1 encoded protein is highly related to the POU domain potentially encoded by the rat brain-3 sequence and to that of the Drosophila I-POU protein; outside of the POU region, RDC-1 is unrelated to any previously characterized protein. The RDC-1 gene is expressed almost exclusively in normal tissues and transformed cells of neural origin. In the developing mouse and human fetus, RDC-1 is expressed in a spatially and temporally restricted pattern that suggests a critical role in the differentiation of neuronal tissues. In addition, RDC-1 is expressed in a unique subset of tumors of the peripheral nervous system including neuroepitheliomas and Ewing's sarcomas but not neuroblastomas. Based on its unique structural characteristics and expression pattern, we discuss potential functions for the RDC-1 protein.